Porcine circovirus type 2 DNA detection in the uterine tissue of gilts in relation to endometritis and the number of leukocyte subsets in the endometrium. (January 2016) - Limsaranrom, Chutimun; Wangpeerawong, Yanika; Phetpa, Phajongporn; Luangaram, Jidapa; Pearodwong, Pachara; Tummaruk, Padet
Abstract The aim of the present study was to determine the prevalence of porcine circovirus type 2 (PCV2) DNA-positive uterine tissues in gilts in relation to endometritis and the number of leukocyte subsets in the endometrium. Uterine tissues from 32 Landrace × Yorkshire gilts were investigated. The gilts were classified according to both macroscopic and microscopic examination of the endometrium into three groups: normal (n = 13), acute endometritis (n = 11) and chronic endometritis (n = 8). Reproductive cycle was defined according to the ovarian appearance as follicular, luteal and inactive phases. PCV2 DNA was determined using polymerase chain reaction. The number of leukocyte subsets, including lymphocytes, neutrophils, eosinophils, macrophages and plasma cells, in the epithelium, subepithelium and glandular layer of the endometrium was carefully evaluated. It was found that PCV2 DNA was detected in 34.4 % (11/32) of the uteri. According to the lesion of endometritis, PCV2 DNA was detected in 53.9 % (7/13) of normal uteri, 36.4 % (4/11) of acute endometritis, and 0.0 % (0/8) of chronic endometritis (P = 0.038). The PCV2 DNA was detected in 55.0 % (5/9), 20.0 % (4/20) and 66.7 % (2/3) of tissues in follicular, luteal and inactive phases, respectively (P = 0.081). Leukocyte subsets in all tissue layers of the endometrium did not differ significantly between the uterine tissues with and without PCV2 DNA detection (P > 0.05). These findings indicate that PCV2 exists in the reproductive organs of the gilts. The PCV2 persistence can be a risk factor for transmission of the virus to negative sows and potentially cause reproductive failures. Nevertheless, the influence of PCV2 natural infection on the reproductive function of gilt still requires further investigation.